Berigtigelse af en Meddelelse i nye landoeconomiste Tidenders 6 B. 2H. Side 222-228. - Rønne, B. F. (Tidsskrift for Landøkonomi, 2018)
Berigtigelse af en Meddelelse i nye landoeconomiste Tidenders 6 B. 2H. Side 222-228.